2011
DOI: 10.3109/00498254.2011.558933
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of verapamil in diabetic rats induced by combination of high-fat diet and streptozotocin injection

Abstract: The aim of this study was to investigate effects of type 2 diabetes on the pharmacokinetics of verapamil after intravenous administration. Diabetes mellitus (DM) rats were induced by combination of high-fat diet (HFD) and streptozotocin. Plasma concentrations of verapamil in DM rats, rats fed with HFD, and control (CON) rats were measured after intravenous administration of 1 mg/kg verapamil and corresponding pharmacokinetic parameters were estimated. Area under the plasma concentration in DM rats was signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…Accumulating reports have shown that diabetes alters the metabolism rates of drugs via affecting activities and expressions of CYP450s and drug transporter in the liver [15,17,20,35] . Simvastatin, a substrate of Cyp3 and Oatp2/OATP1B1, is often used for improving hypercholesterolemia associated with DM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating reports have shown that diabetes alters the metabolism rates of drugs via affecting activities and expressions of CYP450s and drug transporter in the liver [15,17,20,35] . Simvastatin, a substrate of Cyp3 and Oatp2/OATP1B1, is often used for improving hypercholesterolemia associated with DM.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that OATP1B1 plays a clinically important role in the hepatic elimination of several drugs including statins, via mediating the hepatic uptake [11][12][13][14][15] . Both clinical trials and animal experiments have demonstrated that DM may alter the pharmacokinetic behaviors of some drugs via regulating the expressions and activities of cytochrome P450s (CYP450s) and drug transporters in the liver [16][17][18][19][20][21][22] . Breast cancer resistance protein (Bcrp) and multidrug resistance-associated protein 2 (Mrp2) have also been reported to mediate statin transport [11,23,24] .…”
Section: Introductionmentioning
confidence: 99%
“…Experimental type 2 diabetic rats were induced by combination of high-fat diet and low-dose STZ injection according to a method described previously (Reed et al 2000, Chen et al 2011. Following an acclimation period of 3 days, the rats were assigned randomly to three groups: control (CON) group, high-fat diet-fed (HFD) group, and diabetic (DM) group.…”
Section: Induction Of Experimental Diabetes In Rats and Gts Treatmentmentioning
confidence: 99%
“…Hepatic microsomes of rats were prepared according to the methods described previously [23,31] . Paroxetine metabolism in microsomes was investigated using the substrate depletion approach described by Obach [32] .…”
Section: Metabolism Of Paroxetine In Hepatic Microsomesmentioning
confidence: 99%
“…Diabetic (DM) rats were induced by the combination of a high-fat diet and low-dose STZ injection according to a previously described method [23,24] . Briefly, high-fat diet (HFD) rats and DM rats were both fed with a high-fat diet that consisted of 15% lard (w/w), 5% sesame oil, 20% sucrose, 2.5% cholesterol and 57.5% normal chow.…”
Section: Animals and Treatmentmentioning
confidence: 99%